ACTIVITY TEST OF CUO-ZNO-AL2O3 (CZA) CATALYST FOR DIRECT SYNTHESIS OF DME IN BATCH REACTOR - Retno Wulandary, Indah
The uncontrolled use of oil-based fuels for transportation, household, and industrial purposes was the main cause of the depletion of oil and gas in Indonesia. Besides, the large amount of LPG imports that exceed 50% of domestic LPG production in Indonesia was encouraging the government to obtain alternative energy. One of the government's innovations was producing dimethyl ether (DME) from synthetic gas obtained through the coal gasification process. In this study, DME was obtained directly from synthetic gas using CuO-ZnO-Al2O3 (CZA) and CuO-ZnO-MgOAl2O3 (CZMA5) bifunctional catalysts. The objective of this research was to develop of CZA bifunctional catalyst and its modifying used the co-precipitation method. The research was carried out in three steps: (1) the synthesis of catalysts, (2) activation of catalyst, and (3) catalyst activity tests. In this research, bifunctional catalyst was modified with an additional MgO of 5% (by weight) on the CZA catalyst. The co-precipitation method formed a raw catalyst. The next step was activated raw catalyst using reducing gas that contained 5% H2, 95% N2 and produced Cu-ZnO-Al2O3 and Cu-ZnO-MgO-Al2O3 bifunctional catalysts. After that, the catalyst was tested for its activity for the direct synthesis of DME. The feed of the reactor was syngas that contains 65% H2, 28% CO, 7% N2. A fixed bed tubular reactor with a diameter of 2,4 cm and a height of 43,4 cm was used for the activity test of the catalyst. DME direct synthesis was carried out at 260?280?, and 10?20 bar. The downstream of the reactor was analyzed using gas chromatography. The experiment showed the activity of the CZA catalyst was better than CZMA5. The maximum CO and H2 conversions obtained were 91,01% and 82,90% at 280?, 15 bar using the CZA bifunctional catalyst. Yield DME obtained was also low, amounting to 0,12% by using the CZA bifunctional catalyst at 260?, 15 bar.